2018
DOI: 10.1037/xan0000175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stimulus duration on over-selectivity: Evidence for the role of within-compound associations.

Abstract: The phenomenon whereby behavior becomes controlled by one aspect of the environment at the expense of other aspects of the environment (stimulus overselectivity) is widespread across many intellectual and developmental disabilities. However, the theoretical mechanisms underpinning overselectivity are not understood. Given similarities between overselectivity and overshadowing, exploring overselectivity using associative learning paradigms might allow better theoretical understanding of the phenomenon. Three ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 57 publications
(187 reference statements)
1
12
0
Order By: Relevance
“…Again, we observed a robust overshadowing effect in the group Trace0 (with no trace between signals and outcomes), but this cue competition effect was abolished by interposing a trace of 3 s. This result extends those observed in Experiment 3A, using widely spaced training trials (that is, increasing the ITI). As we noted before, the rodent literature suggests that spaced trials promote overshadowing (Reynolds & Reed, 2018. Crucially, using short-signals and long ITI, factors that promote cue competition, interposing a trace of 3 s consistently abolished the overshadowing effect.…”
Section: Testsupporting
confidence: 63%
See 2 more Smart Citations
“…Again, we observed a robust overshadowing effect in the group Trace0 (with no trace between signals and outcomes), but this cue competition effect was abolished by interposing a trace of 3 s. This result extends those observed in Experiment 3A, using widely spaced training trials (that is, increasing the ITI). As we noted before, the rodent literature suggests that spaced trials promote overshadowing (Reynolds & Reed, 2018. Crucially, using short-signals and long ITI, factors that promote cue competition, interposing a trace of 3 s consistently abolished the overshadowing effect.…”
Section: Testsupporting
confidence: 63%
“…In Experiment 3A, we observed a lack of overshadowing in the group Trace3 (with a 3 s trace between the signal and the outcome) regardless of the use of a short signal (2 s rather than the 5-s signal used in previous experiments) which is supposed to promote overshadowing (Reynolds & Reed, 2018;. Another factor that has proved to modulate the effect of Overshadowing is the distribution of trials during training.…”
Section: Experiments 3bmentioning
confidence: 60%
See 1 more Smart Citation
“…A further limitation is that it is unclear whether the current observations generalise to different types of compound stimuli, and whether factors like similarity, proximity, etc., play a role. Certainly, it has been suggested that within-compound associations, which would be dependent upon such factors, are implicated in the development of over-selective responding (Reynolds & Reed, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, longer exposure may allow adequate processing of both categories, allowing the integration of the symbol cues. Previous work suggests that long stimuli attenuate overshadowing in rats (Sissons et al, 2009) and reduce overselectivity in humans (Reynolds & Reed, 2018). However, we are not aware of studies exploring whether the signal length is a factor determining overshadowing in humans.…”
Section: Methodsmentioning
confidence: 99%